Collaborative Counseling Model in Religious Learning for People with Disabilities - Haliq, Fathol; Tatik Hidayati (Universitas Islam Negeri Madura, 2025)
This study examines the collaborative guidance and counseling model for individuals with disabilities in a religious education environment in Madura. This study addresses key questions: How do individuals with disabilities learn Islamic teachings? How do they fulfill religious obligations? What is the role of parents, siblings, and peers in providing social support? This study used a qualitative approach. Data were collected through in-depth interviews, participant observation, and document analysis. The researcher conducted direct observations that allowed for in-depth experiences with families, educators, and students. Data triangulation was obtained through various sources, including focus group discussions (FGDs) with teachers, parents, and individuals with disabilities. The location of the study was SLB Api Alam Tlanakan. The findings indicate that (1) religious values ​​are internalized in both structured (Special School) and unstructured (family and social environments) environments; (2) economic constraints affect the family's ability to support religious education; and (3) religious education plays a unique role in shaping the behavior and identity of individuals with disabilities. This study highlights the importance of community involvement in religious education for individuals with disabilities.